The Deep Mining Era: Genomic, Metabolomic, and Integrative Approaches to Microbial Natural Products from 2018 to 2024 - Zhaochao Wang; Juanjuan Yu; Chenjie Wang; Yi Hua; Hong Wang; Jianwei Chen (Marine Drugs)
Over the past decade, microbial natural products research has witnessed a transformative “deep-mining era” driven by key technological advances such as high-throughput sequencing (e.g., PacBio HiFi), ultra-sensitive HRMS (resolution ≥ 100,000), and multi-omics synergy. These innovations have shifted discovery from serendipitous isolation to data-driven, targeted mining. These innovations have transitioned discovery from serendipitous isolation to data-driven targeted mining. Genome mining pipelines (e.g., antiSMASH 7.0 and DeepBGC) can now systematically discover hidden biosynthetic gene clusters (BGCs), especially in under-explored taxa. Metabolomics has achieved unprecedented accuracy, enabling researchers to target novel compounds in complex extracts. Integrated strategies—combining genomic prediction, metabolomics analysis, and experimental validation—constitute new paradigms of current “deep mining”. This review provides a systematic overview of 185 novel microbial natural products discovered between 2018 and 2024, and dissects how these technological leaps have reshaped the discovery paradigm from traditional isolation to data-driven mining.